Manliness, violation, and laughter: rereading the space and context of the Eurymedon vase - Llewellyn-Jones, Lloyd (Journal of Greek Archaeology, 2017)
The focus of this short study is a well-known and much discussed object: a red-figured type VII oinochoe, dated to the mid-460s BC and attributed (perhaps) to the Triptolemos Painter, or certainly to his circle. Since Konrad Schauenburg’s 1975 publication of the artefact, it has been known as the ‘Eurymedon Vase.’ It has rightly been classified as ‘unique’ by Amy Smith and although it is beyond the scope of this study to spend too much space re-rehearsing the scholarship on the vase in any detail, a general overview might prove profitable for what follows below.